Distinct alterations of fecal microbiota refer to the efficacy of adalimumab in Crohn’s disease - Chen, Liang; Lu, Zhanjun; Kang, Dengfeng; Feng, Zhongsheng; Li, Gengfeng; Sun, Mingming; Liu, Zhanju; Wu, Wei; Fang, Leilei (Frontiers in Pharmacology, 2022)
Background & Aims: Adalimumab（ADA) is currently used in the treatment of patients with Crohn’s disease (CD). However, its regulation on fecal microbiota is still not fully understood. Methods: A retrospective analysis was conducted on 115 patients with CD who received treatment with ADA for 12 weeks at inflammatory bowel disease center in the Shanghai Tenth People's Hospital and department of Gastroenterology in Shanghai General Hospital. The crohn’s disease activity index (CDAI) evaluation was applied to patients before ADA therapy at week 0 and week 4, 8, 12. Clinical remission (CR) was defined as a CDAI <150. All patients underwent an ileocolonoscopy or enteroscopy at week 0 and week 12. Crohn’s Disease Endoscopic Index of Severity (CDEIS) scores were calculated by 2 experienced physicians to assess endoscopic activity. Mucosal healing (MH) was assigned a CDEIS score of between 0 and 3. Fecal samples were collected in 8 CD patients at baseline and week 12, respectively, and microbiota was analyzed using 16S sequencing. Results: At week 12, CR was achieved by 70.6% (72/102) of patients with active CD. A total of 47.1% (48/102) of patients with active CD attained MH, among which, 56.6% (30/53) of patients with mildly active CD (3 ≤ CDEIS < 9) and 48.0% (12/25) of moderately active CD patients (9 ≤ CDEIS < 12) attained MH, but only 25.0% (6/24) achieved MH in severely active CD patients (CDEIS ≥ 12). Unexpectedly, we found at the genus level an increase in protective microbiotas (e.g., Barnesiella, Anaerostipes, Tyzzerella, Lachnoclostridium and Lachnospiraceae_unclassified) but a decrease in pathogenic bacteria (Escherichia-Shigella) in the fecal samples of ADA-responsive group (ADA-R) compared with those in ADA-nonresponsive group (ADA-NR). Notably, the gene bglX coding β-glucosidase and gph encoding phosphoglycolate phosphatase were enriched in fecal samples of ADA-R. Conversely, the abundance of genes coding ATP-binding cassette (ABC) transporter system proteins was significantly enriched in fecal samples of ADA-NR compared with that in ADA-R. Conclusions: This study reveals that ADA markedly improves clinical remission and induces MH in mild-to-moderate active CD patients and that distinct changes in gut microbiota can be used to predict the efficacy of ADA.